Diminazene aceturate mitigates cardiomyopathy by interfering with renin-angiotensin system in a septic rat model - Zhaoqing Lu; Di Wu; Zheng Wang; Hanyu Zhang; Yufan Du; Guoxing Wang (BMC, 2022)
Abstract Background There were limited studies investigating treatments of septic cardiomyopathy (SCM), which is a common complication during sepsis. A septic rat model created by cecal ligation and puncture (CLP) was used to investigate the effects of diminazene aceturate (DIZE) in SCM. Methods A total of 151 Wistar rats were randomly assigned into the sham, CLP, or CLP + DIZE group. Data evaluated postoperatively at 6, 12, 24, and 48 hours included: cardiac function; plasma concentrations of tumor necrosis factor-alpha (TNF-α), interleukin-6, angiotensin-(1-7) [Ang-(1-7)], angiotensin II (AngII), troponin I, and brain natriuretic peptide; expression levels of myocardial Ang-(1-7), angiotensin-converting enzyme (ACE), ACE2, and angiotensin type 1 and Mas receptors; and histological changes. Results We found that the CLP + DIZE group had a lower mortality compared to the CLP group (38.5% versus 61.5%) within 48 h postoperatively, although without statistical significance. In contrast to the sham group, the CLP group had decreased cardiac functions, increased myocardial injuries, and higher TNF-α levels, which were ameliorated in the CLP + DIZE group. Furthermore, administration of DIZE could reverse the decreases of myocardial Ang-(1-7) and ACE2 expressions in the CLP group, which finally minimized the myocardial microstructure disruptions. Conclusions It was concluded that DIZE could mitigate the development of SCM and preserve cardiac function during sepsis possibly by interfering with the renin-angiotensin system through promoting myocardial ACE2 expression and restoring local Ang-(1-7) levels.